Tooth Agenesis in Human Population: Treatment Considerations in Subjects with Tooth Agenesis - Shoaib, Ahmad; Ahmed, Bilal (Pakistan journal of medical research, 2023)
Abstract Background: Tooth agenesis presents itself with one or more lost teeth and is one of the foremost common formative irregularities of the human dentition. Being polygenetic, it can occur entirely isolated or in conjunction with other syndromes. Methodology: Research papers published in English from 1950-2020 were searched. Studies on non-human subjects and medically marginalized patients were excluded. Results: Tooth agenesis is a commonly occurring congenital dental abnormality. This literature emphasizes on a multidisciplinary approach and a logically planned treatment with a precise well controlled follow up. When providing treatment for patients with tooth agenesis, several important considerations come into play. Thoroughly assessing the patient's oral health, collaborating with dental specialists to determine the best course of action, and developing individualized treatment plans are crucial steps to achieve optimal outcomes and ensure patient satisfaction. By addressing these factors, dental professionals can effectively navigate the unique challenges presented by tooth agenesis and provide comprehensive care for their patients. Conclusion: Different treatment modalities and their resultant outcomes on the quality of life of hypodontia people have been discussed. A multi-disciplinary approach is vital to improve the oral health related quality of life for these patients.